The generalized equity and exact credibility premiums with examples - Djebar, Ahlem (2024)
We investigate a more generalized alternative to the conventional credibility premium that results from squared-error loss, namely, equitable credibility premium (Promislow and Young, 1999), based on exponential family, and we derive an accurate credibility for Bühlmann model with an example. We provide sufficient conditions for accurate credibility and expand a generalised formula for the credibility weight in specific circumstances. In this article, we expand upon the research conducted by Promislow and Young (2000) to include situations where an actuary is provided with data regarding a policyholder who has a more extensive exponential family. In the first section, we established our notation and reformulation of exact credibility for a Bühmann model. We derive the class of general equitable credibility premiums in the second section.